2013
DOI: 10.1177/0266666913513279
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perceived risks and switching barriers on the intention to use smartphones among non-adopters in Korea

Abstract: Timely diffusion of IT products is critical to the success of technology companies. However, many IT products fail to attain the critical mass required for profitability. Although several studies have identified perceived usefulness as the primary factor in IT adoption, statistics indicate that some Korean consumers avoid IT products despite understanding their utility. This study empirically examines the effects of perceived risks and switching barriers on Korean non-adopters’ intention to use smartphones. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Therefore, future work may consider studying the relationship between intentions and actual use behavior. In addition, investigating factors of barriers as well as continuous intention of using mobile learning can improve understanding of use retention (Gan, 2015;Kim et al, 2015). This will enable greater implications for research and practice for future studies.…”
Section: Limitation and Future Researchmentioning
confidence: 99%
“…Therefore, future work may consider studying the relationship between intentions and actual use behavior. In addition, investigating factors of barriers as well as continuous intention of using mobile learning can improve understanding of use retention (Gan, 2015;Kim et al, 2015). This will enable greater implications for research and practice for future studies.…”
Section: Limitation and Future Researchmentioning
confidence: 99%
“…For example, smartphone users may have a poor experience of browsing mobile websites because they have poor navigation, they are not fast, or designed for a smartphone (Kim and Sundar, 2014;Safer, 2014). In addition, both Aldhaban et al (2015)'s study and Kim et al (2015)'s studies claimed that performance of the smartphone affects the BI of customers. The lodging industry should focus on these issues as the recent study found the number of customers using the hotel apps are not increasing in spite of hotel companies' efforts (Criteo, 2018).…”
Section: Perceived Equipment Riskmentioning
confidence: 99%
“…Switching barriers referred to a series of factors that make it difficult or expensive for a customer to switch to other providers [49,51]. Switching barriers has two indicators in term of external comparison and internal obstacle (i.e.…”
Section: User Experience Switching Barriers Loyaltymentioning
confidence: 99%
“…Switching barriers is another factor that might influence customer loyalty. Switching barriers refer to a series of factors that make it difficult or expensive for a customer to switch to another service provider [49,51,52]. Switching barriers can be developed by user experience and it able to increase user dependence on the existing provider [7,8,60].…”
Section: User Experience Switching Barriers Loyaltymentioning
confidence: 99%